2011
DOI: 10.1159/000324697
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Prognostic Role of Nighttime Blood Pressure and Nondipping Profile on Renal Outcomes

Abstract: Different studies have addressed the predictive role of nighttime hemodynamics on cardiovascular and renal outcomes, although nocturnal blood pressure (BP) phenotypes (i.e. nondipping pattern and absolute nocturnal BP) have been found to be predictive of worse health outcomes. Furthermore, differences in both examined populations – ranging from healthy and younger subjects to those with overt cardiovascular disease – and study design (i.e. cross-sectional or longitudinal) make the interpretation of the suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 217 publications
2
19
0
2
Order By: Relevance
“…Our work and evidence from the literature [18,31,32,34,35] supports the use of categories on the basis of absolute blood pressures. It is more straightforward and it may be easier to apply in daily clinical practice.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our work and evidence from the literature [18,31,32,34,35] supports the use of categories on the basis of absolute blood pressures. It is more straightforward and it may be easier to apply in daily clinical practice.…”
Section: Discussionsupporting
confidence: 72%
“…Also, in dippers and nondippers with nocturnal hypertension, the prevalence of subclinical target organ damage was similar [18]. Tsioufis et al [31,32] found the absolute night-time blood pressure to be better than dipping status for predicting both cardiovascular and renal outcomes in two systematic reviews. De La Sierra et al [33] reported on the prevalence of cardiovascular risk factors in patients classified by dipping and nocturnal hypertension status.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, most but not all cross-sectional studies have found nocturnal BP levels and a non-dipping profile of BP to be associated with impaired renal function (assessed either with microalbuminuria or eGFR) and with renal damage (severity of CKD and presence of ESRD), as recently shown in a systematic review of the relevant literature [85].…”
Section: Short-term Bpv: Its Significance For CV and Renal Prognosismentioning
confidence: 86%
“…This is largely attributed to ABPM providing information on factors such as non-dipping status and BP variability, which have been shown to predict target-organ damage, but cannot be captured with clinic BP readings [16] . Current evidence derived from numerous observational studies in a wide range of populations (such as patients with essential hypertension, type 2 diabetes mellitus, and the elderly) clearly suggests the higher prognostic value of ABPM also for renal outcomes, including progression of albuminuria, decline of estimated glomerular function (eGFR), and incident ESRD, as recently summarized elsewhere [17] . Moreover, with regard to patients with CKD and ESRD, observations for increased frequency of nondipping status and altered BP variability associated with target-organ injury [18,19] have progressively evolved to several pieces of evidence, suggesting superiority of ABPM in predicting cardiovascular events and mortality [20,21] .…”
mentioning
confidence: 95%